2021
DOI: 10.1002/cphc.202100508
|View full text |Cite
|
Sign up to set email alerts
|

Improving Reproducibility in Hydrogen Storage Material Research

Abstract: This article therefore describes the measurement of hydrogen sorption and covers the required experimental procedures, aspects of troubleshooting and recommended reporting guidelines, with a view of helping improve reproducibility in experimental hydrogen storage material research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 126 publications
(206 reference statements)
0
26
0
Order By: Relevance
“…A relevant issue in assessing experimental data from a diverse array of sources is to understand what level of reproducibility is obtained among distinct measurements. This issue is of course important in many areas of materials chemistry and engineering. Several recent efforts have been coordinated to examine this issue for measurements of adsorption equilibrium. Gasparik et al performed an interlaboratory study for methane, CO 2 , and ethane isotherms in shales, highlighting the importance of standardized calibration and measurement protocols as well as a precise control of the experimental conditions.…”
Section: Introductionmentioning
confidence: 99%
“…A relevant issue in assessing experimental data from a diverse array of sources is to understand what level of reproducibility is obtained among distinct measurements. This issue is of course important in many areas of materials chemistry and engineering. Several recent efforts have been coordinated to examine this issue for measurements of adsorption equilibrium. Gasparik et al performed an interlaboratory study for methane, CO 2 , and ethane isotherms in shales, highlighting the importance of standardized calibration and measurement protocols as well as a precise control of the experimental conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In line with the issues raised above, Broom and Hirscher discussed the necessary steps for reproducible results in hydrogen storage research [15].…”
Section: Characterization Methods: Old New and Their Pitfallsmentioning
confidence: 97%
“…However, analysis of the literature data also points out to several weaknesses in applying traditional characterization methods that have not yet been tuned for current nanosized materials [15,34,37,38]. For instance, AB (ammonia borane) hydrogenation studies showed many inconsistencies [38].…”
Section: Characterization Methods: Old New and Their Pitfallsmentioning
confidence: 99%
See 2 more Smart Citations